'Everything' disappears … reflexive design and norm-critical intervention in the digitalization of cultural heritage. Issue 10 (24th August 2019) - Nyhlén, Sara; Gidlund, Katarina L.
ABSTRACT: According to narrative trends, digitalization has the potential to deconstruct both power structures and practices of exclusion in society. What we argue here is that this deconstruction is not the result of digitalization alone, it is dependent on how digitalization is done. On the contrary, digitalization has often resulted in reproduction instead of transformation and deconstruction, i.e. digitalization tend to uphold practices instead of challenging them. Being slightly more provocative, what becomes digitalized is often what we can easily capture and understand. Similarly, when we open up for an increased participation in the creation of digital artifacts (sometimes expressed as demand-driven, citizen-centered, or participatory development), those participating in digitalization are often already known; the use of already established contact channels making them easy to reach and connect with. Such logics raise questions about the intersections of norms and power and the potential transformative character of digitalization. The aim of this paper is to, through a theoretical framework combining critical information systems, policy enactment and norm critical design, introduce a reflexive design method to gently provoke norms. We analyze the need to intervene in the everyday practices of digitalization. This is done in an empirical case study of the making of a regional digital cultural heritage portal. The results indicate that digitalization needs norm critical interventions to change existing practices and prevent norm reproduction. Otherwise, as in this case of the digitalization of cultural heritage, digitalization runs the risk of strengthening existing power structures and excluding practices instead of challenging them.